Age and growth of Oreochromis niloticus (Perciformes: Cichlidae) in Mexico - Gómez-Márquez, José Luis (Universidad de Costa Rica, 1998)
Age and growth of Oreochromis niloticus from Lagoon of Coatetelco, Morelos State, Mexico were studied from January through December, 1993. Scales of 318 specimens were collected. Modal length at capture was 10. 5 -11. 5 cm standard length. Scales rings were forrned during December. Back-calculated lengths-at-age showed no significant differences by sexo Four check marks were recorded. According to the growth curve parameters for population, the fish grow at a low rate (k=O.07) until they achieve a size (Loo) of 2 9. 19 cm. Length-frequency analysis (Bhattacharya's Gaussian component deterrnination procedure) do not differ significantly (t-student, p